A pair of blue eyes - Jain, Pramila (New Delhi : Pearl Books, 2008)
A work of Indian English fiction exploring themes of love, relationships, and contemporary social life.
Novel
Keywords: Indic fiction (English); English fiction -- zIndia; Love stories -- India -- Fiction; India -- Social life and customs -- Fiction